Larimele Burger: Aplikasi Mobile Pemesanan Makanan Cepat Saji Berbasis Android untuk Meningkatkan Efisiensi Pelayanan Restoran - Nugraha, Windu Yoga; Pratama, Muhammad Rifky Anugrah; Aprian, Wandy; Payangan, Juniati Tiku (PT. Lontara Digitech Indonesia, 2025)
The evolution of modern lifestyles demands a fast, reliable, and seamless fast-food ordering process. Larimele Burger is an Android application we developed to facilitate efficient fast-food ordering. Its key features include instant registration and login, a persistent shopping cart, and product recommendations by the admin (administrator rating). Evaluation was conducted through a Black-Box Testing, confirming that all functions operate according to specifications. The application offers a practical solution for ordering burgers at the restaurant.